2019
DOI: 10.1016/j.proci.2018.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Darrieus–Landau instability and Markstein numbers of premixed flames in a Hele-Shaw cell

Abstract: Hydrodynamic flame instabilities are studied in a Hele-Shaw burner. By studying the development of perturbations, starting from a 2D Bunsen flame at the top of the burner, growth rates are measured for propane and methane-air mixtures, and compared to theoretical predictions. It is found that the dispersion relation in a Hele-Shaw cell has the same dependence with wavenumber σ = k − k 2 as the one predicted in tubes. Markstein numbers relative to fresh gases are obtained for propane and methane flames and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 25 publications
(18 reference statements)
3
22
0
Order By: Relevance
“…When focusing on the topology of the flame interface, both parametric restabilization and parametric resonance are possible to be forced, as predicted by the Searby and Rochwerger [8] theory. It has been shown that the plate modes may be excited by the flame propagation itself and are certainly responsible for the flame speed oscillations with unexpected frequencies observed in recent experiments [18,26,27].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…When focusing on the topology of the flame interface, both parametric restabilization and parametric resonance are possible to be forced, as predicted by the Searby and Rochwerger [8] theory. It has been shown that the plate modes may be excited by the flame propagation itself and are certainly responsible for the flame speed oscillations with unexpected frequencies observed in recent experiments [18,26,27].…”
Section: Discussionmentioning
confidence: 96%
“…We analyze the downward propagation of propane-air flame with equivalence ratios in the range 0.7 to 1.5 with each plates set. This range corresponds to the range where the flame can propagate inside the Hele-Shaw cell of 5mm gap without thermal extinction due to heat loss on the walls [18]. Acoustic instability usually appears during propagation in tubes [8].…”
Section: Self Induced Vibro-acoustic Oscillationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experiments are carried out in a Hele-Shaw burner [14][15][16][17][18][19][20]. The apparatus used here is made of two borosilicate glass plates (1500 ×500 ×5mm)…”
Section: Experimental Set-upmentioning
confidence: 99%